GENDER SELF EFFICACY TEKANAN KETAATAN KOMPLEKSITAS TUGAS DAN PENGALAMAN AUDITOR TERHADAP AUDIT JUDGEMENT - Septiaji, Bayu Candra; Hasymi, Muhammad (Universitas Muhammadiyah Palembang, 2021)
The quality of the audit judgment produced by the auditor determines the quality of the overall audit results. This study aims to determine the effect of gender, self-efficacy, obedience pressure, task complexity, and auditor experience on audit judgment. This study uses quantitative methods with a sample size of 104 internal auditors at the Inspectorate General of the Ministry of Finance. The data used are primary data obtained through distributing questionnaires and then processed using the IBM SPSS version 25 application. The results of the study concluded that self-efficacy and auditor experience had a positive and significant effect on audit judgment. This shows that the competence, experience, and expertise of auditors have a positive and significant effect on the resulting audit judgment. Meanwhile, obedience pressure has a negative and significant effect on audit judgment. Pressure for obedience can come from superiors and auditors. Meanwhile, gender and task complexity have no effect on audit judgment. Audit assignments are preceded by a comprehensive audit planning process and support from the unit related to gender responsive policies that support the assignment.